The online healthcare community : pioneering inclusive healthcare support in developing countries - Panda, Amaresh; Mohapatra, Sanjay (Emerald Publishing Limited, 2024)
The shift from in-person to online health services has now become a driving force in delivering efficient healthcare, especially in developing countries where this need is imperative. The Online Health Community (OHC) serves as a virtual platform where individuals, including patients, medical professionals, caregivers, and families, can learn about illnesses, offer support, and connect with others in similar situations. In The Online Healthcare Community: Pioneering Inclusive Healthcare Support in Developing Countries, authors Amaresh Panda and Sanjay Mohapatra lay the foundation for exploring virtual healthcare practices in India by presenting an overview of the online healthcare concept within the Online Healthcare Community (OHC). They begin by developing a comprehensive literature review, evaluating existing studies, identifying key variables, and tracing the systematic evolution spread over years for OHC. Chapters go on to employ an empirical-deductive approach with a quantitative orientation to evaluate relationships among variables, focusing on stakeholder activities within the online healthcare domain. Their findings offer industry insights and highlight the integral role OHC will play in the future of healthcare. Essential for students, researchers, and healthcare professionals keen on understanding the changing healthcare landscape, this work explores the shift to virtual healthcare emphasizing OHC's engagement, expertise sharing, and capacity for industry transformation, especially across tech-driven nations such as India.
Includes index.
Keywords: Internet in medicine.; Health services accessibility.; Business & Economics -- Industries -- Healthcare.; General practice / Family medicine.; Industry and industrial studies.; Health systems and services.; elektronické knihy; electronic books